Turner syndrome: fertility counselling in childhood and through the reproductive lifespan. Issue 1 (24th February 2023) - Bollig, Kassie J.; Mainigi, Monica; Senapati, Suneeta; Lin, Angela E.; Levitsky, Lynne L.; Bamba, Vaneeta
Abstract : Purpose of review: The potential for fertility in Turner syndrome has improved in recent years. Understanding of associated risks and approaches is important for the care of girls and women with this condition. This review focuses on reproductive health, fertility options and appropriate counselling for women with Turner syndrome and their families. Recent findings: Women with Turner syndrome have rapidly declining ovarian function beginning in utero . Therefore, counselling regarding fertility concerns should begin at a young age and involve discussion of options, including ovarian tissue cryopreservation, oocyte preservation and use of nonautologous oocytes. Clinical guidance on fertility management and pregnancy risk assessment based on karyotype, associated comorbidities and fertility is still not fully data driven. Realistic expectations regarding reproductive options and associated outcomes as well as the need for multidisciplinary follow-up during pregnancy are crucial to the ethical and safe care of these patients. Summary: Fertility care in women with Turner syndrome is evolving as current management techniques improve and new approaches are validated. Early counselling and active management of fertility preservation is critical to ensure positive and well tolerated reproductive outcomes.